(untitled) (International Journal of Applied Research in Management and Economics, 2020)
The knowledge of emotions is essential in a wide spectrum of designs created for the customer (e.g. product design, service design, graphic design, food design). The complexity of designing a product-service system to provoke intended emotions involves the need to formulate a shareable, natural, and unambiguous language. This paper presents a language framework to discuss emotions in product innovation, which is composed of three key concepts: the human-product emotional interactions, a categorization of positive emotions and the emotional-jobs-to-be-done. An exploratory survey with an international community of designers has been implemented in order to review the acceptance and understanding of this framework. The results of the exploratory survey have been the basis of the final refinement of the proposed language, which consists of 1) three categories of human-product emotional interaction, 2) 19 positive emotion types, and 3) 19 emotional jobs-to-done.